Patients with LRBA deficiency show CTLA4 loss and immune dysregulation responsive to abatacept therapy - AYDINER, ELİF (AMER ASSOC ADVANCEMENT SCIENCE, 2015)
Mutations in the LRBA gene (encoding the lipopolysaccharide-responsive and beige-like anchor protein) cause a syndrome of autoimmunity, lymphoproliferation, and humoral immune deficiency. The biological role of LRBA in immunologic disease is unknown. We found that patients with LRBA deficiency manifested a dramatic and sustained improvement in response to abatacept, a CTLA4 (cytotoxic T lymphocyte antigen-4)-immunoglobulin fusion drug. Clinical responses and homology of LRBA to proteins controlling intracellular trafficking led us to hypothesize that it regulates CTLA4, a potent inhibitory immune receptor. We found that LRBA colocalized with CTLA4 in endosomal vesicles and that LRBA deficiency or knockdown increased CTLA4 turnover, which resulted in reduced levels of CTLA4 protein in FoxP3(+) regulatory and activated conventional Tcells. In LRBA-deficient cells, inhibition of lysosome degradation with chloroquine prevented CTLA4 loss. These findings elucidate a mechanism for CTLA4 trafficking and control of immune responses and suggest therapies for diseases involving the CTLA4 pathway.
Keywords: COMMON VARIABLE IMMUNODEFICIENCY; REGULATORY T-CELLS; LONG-TERM SAFETY; RHEUMATOID-ARTHRITIS; MUTATIONS; ACTIVATION; DISORDERS; DISEASE; GENE; LYMPHOPROLIFERATION